Pengaruh Leverage, Good Corporate Governance dan Sistem Pengendalian Manajemen Terhadap Pengungkapan Sustainability Report: Studi Kasus pada Industri Pertambangan yang Tercatat di Bursa Efek Indonesia Periode 2018-2021 - Yani Febriawaningsih; Yanti; Trias Arimurti (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
The aim of this research focuses on leverage, good corporate governance and management control systems for sustainability report disclosures. The method used in this research is a descriptive quantitative method with data taken using a purposive sampling technique from financial reports and sustainability reports of mining companies listed on the Indonesia Stock Exchange, utilizing the Smart PLS version 3.0 application. The results of this research show that the influence of leverage, good corporate governance and management control systems have a positive effect on sustainability report disclosure.